Contribuições de Paulo Freire e Humberto Maturana para a educação ambiental: um olhar intercultural sobre o programa PIBID (UNISC) no curso de formação de professores(as) de Ciências Biológicas - Rosa, Cleni Inês da (2021)
The present doctoral thesis research on Education in the line of Teaching, Knowledge and Professional Development in PPGE of the UFSM, based on semistructured interviews with graduates from the Biological Sciences' course of UNISC who are part of the PIBID Program, has as a main subject the instruction of teachers on Environmental Education of teachers of Biological Sciences. The present research was based on the development of specific goals which were the following: 1) to perform a documentary research on Environmental Education that is being used as guidance for the PIBID Program in general and in UNISC in particular. 2) to get information from a group of teachers that are part of the PIBID-UNISC Program on how Environmental Education was inserted in their initial instruction. 3) to get information from a group of participants of the PIBID Program on how the process of inserting Environmental Education is performed daily at the school where they work or have worked. 4) to identify in the works of Paulo Freire and Humberto Maturana the epistemological and theoretical contributions to understand the environmental matters in the instruction of teachers in general and, especially, the ones of Biological Sciences. In the semistructured interviews for the present research, questionnaires were used with a purported intention of bringing to light information in a freer way, without conditioning it to a probable standardization obtained when only a fixed set of alternatives is offered. I do propose in the research some of the Freirean ideas on Popular Knowledge, Autonomy, Tolerance, Love and Citizenship, with the purpose of identifying certain aspects that may contribute to the instruction of teachers in relation to Environmental matters so that they could be part of their daily work, in an integrated whole with the pedagogic practices built mutually by teachers. I do introduce as well some propositions by Humberto Maturana in relation to a Solidary and Cooperative Environmental Education which, based on two dimensions (intimate and functional), are considered essential in understanding Environmental Education. The present research makes up for a dialogue between the ideas of Paulo Freire and Humberto Maturana so that these two set of ideas form a collaboration to enlarge the epistemological heritage in relation to Environmental Education in the instruction of Biological Sciences' teachers. The final objective is a reaffirmation that the education in general and the Environmental Education in particular need involvement much more than they need contents.